Regional disparities in the European Union: Policy objectives, the poorest regions and multifunctional agriculture - Grbić, Vladimir (Economics of Agriculture, 2010)
The main aim of this paper is to identify regional disparities in the European Union and position of the agriculture in that context. In the paper are analyzed: the first, policy objectives of the EU policies in overcoming the regional problems; second, the proportion of the regional disparities and position of agricultural regions; third, the regional policies of the EU point to solving those problems. It is concluded that the poorest regions of the EU consist mostly agricultural activity and the EU budget for the period 2007-2013 has been extended in order to provide resources for alleviating regional disparities. When the Monetary Union was established apart from traditional motives for implementing a regional policy such as solidarity and facilitating Single Market functioning appeared a new reason. Monetary policy can be helped with regional policy in solving the problem of asymmetric shock.